1993
DOI: 10.1111/j.1574-695x.1993.tb00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of cytokine production during coccidial infections in chickens: colony-stimulating factors and interferon

Abstract: We assayed two classes of immunoregulatory cytokines, colony-stimulating factors (CSF) and interferon (IFN), during and immediately after a primary coccidial infection in chickens. Coccidial infection induces significant alterations in serum colony-stimulating activity (CSA) and these alterations immediately precede the characteristic biphasic leukocytosis. CSA rose sharply during the first 24 h post-inoculation (PI), but returned to control levels by 48 h PI. At this time, we detected an increase in periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…There is a correlation between resistance to these diseases and early and higher IFN-γ production. A high level of IFN-γ production has also been shown in chicken strains that are resistant to coccidiosis [20,90,139]. These observations suggest that chicken lines with an enhanced IFN-γ response are more resistant to some viral and parasitic infections.…”
Section: Cytokinesmentioning
confidence: 75%
“…There is a correlation between resistance to these diseases and early and higher IFN-γ production. A high level of IFN-γ production has also been shown in chicken strains that are resistant to coccidiosis [20,90,139]. These observations suggest that chicken lines with an enhanced IFN-γ response are more resistant to some viral and parasitic infections.…”
Section: Cytokinesmentioning
confidence: 75%
“…Some cytokine activities can also be observed in the blood from chicks challenged with pathogens or immunogens. For example, coccidiosis increases plasma concentrations of TNF-a activity, CSF activity, and interferon (Byrnes et al, 1993b), and Salmonella typhimuriutn lipopolysaccharide increases the plasma concentrations of IL-1 activity in chicks . Presumably, some cytokines are released at the site of challenge in sufficient quantities to make their way into the general circulation, where they may act on distant tissues to coordinate recruitment of new leukocytes and the acute phase response.…”
Section: General Cytokine Nomenclature and Physiologymentioning
confidence: 98%
“…Several reports have described IFN-g -like activity in the CM of cells from Eimeria-infected birds (Prowse & Pallister, 1989;Byrnes et al, 1993;Martin et al, 1994;Breed et al, 1997), both following primary infection and in some cases after repeated challenge. However, some of these studies have detected IFN-g expression from splenocytes from both infected and naṏ ve birds (Martin et al, 1994;Breed et al, 1997), suggesting that splenocytes might not be a useful source of lymphocytes for studying cytokine responses to eimerian infections.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-like activities from antigen-or mitogen-stimulated immune T cells can inhibit the invasion or development of Eimeria tenella in cultured cells (Kogut & Lange, 1988, 1989aProwse et al, 1992). Also, IFN-like activity was shown to be produced by spleen cells from birds previously infected with E. tenella (Prowse & Pallister, 1989) and Eimeria maxima (Byrnes et al, 1993). Recently, Breed et al (1997) showed that peripheral blood lymphocytes (PBL) from E. tenella-infected chickens specifically produce IFNg after in vitro stimulation.…”
Section: Introductionmentioning
confidence: 99%